Resin nano modified glass ionomer cement: a modern dental restoration material: Glass ionomer cement modifikasi resin nano: bahan restorasi dental modern - Aries Chandra Trilaksana; Elizabeth Murniati (Makassar Dental Journal PDGI Makassar, 2020)
GIC is one of the dental materials that has unique properties so that it can be useful as a restoration material and luting material. It has properties such as the ability of this material to chemically bind dentine and enamel through ion exchange mechanisms, as well as the ability to carry out ion exchange with the remaining tooth structure. This leads to the release of fluorideandotherionsinthelongtime,sothismaterialcanpreventcaries.Sinceitsdevelopment,GIChasincreasinglybecome an important part of dental practice to provide care that can maintain tooth structure, remineralize, and maintain aesthetics. GIC nano resin modification is a new development of GIC material that gives natural ionomer glass restoration, enhances aesthetics, provides strength and resistance to wear. This paper is aimed to explain the benefits of combining nano particles into glass ionomer powder in terms of the aspects of antimicrobial activity, their biocompatibility aspects, mechanical and physical aspects, as well as their composition and manipulation.